Islamic Belief and Its Impact on Individual and Society in The Perspective of Surah (Saad) Research on The Beliefs of An Essayist - Abbas Ali Suliman; Mahdi Mahmood Qader (QALAAI ZANIST JOURNAL, 2022)
The theme of monotheism is a major theme in Surah Sad; because monotheism is the basis of belief and its main basis, and the call of all prophets and messengers from Adam to the last Prophet Muhammad (peace is upon them) has been for monotheism. Through a righteous opinion, human being will be happy in the world and the future, and human being will join the prophets and the righteous, and they will avoid anxiety and become a useful and positive individual in society. From this point of view, both researchers discuss the beliefs, importance, characteristics of beliefs and positive traces for reform on individuals and societies. Their research consists of one part and three axes. The first one talks about the concepts, importance, and characteristics of belief, and in the second axis, they give a general definition of Surah Sad, and the third and final axis talks about the role of belief and the impact on individuals and society, and, in the end, they describe some conclusions.